2021
DOI: 10.1002/batt.202100101
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy Nickel‐Cobalt‐Aluminium Oxide (NCA) Cells on Idle: Anode‐ versus Cathode‐Driven Side Reactions

Abstract: Invited for this month's cover picture is the group of Prof. Harry Hoster at Lancaster University. The cover picture illustrates how state of charge (SoC) influences the capacity fade of a widely employed automotive Li‐ion battery chemistry when idle, e.g. when EVs are parked. The chemical degradation is revealed to be aggravated when devices are kept at around 80 % SoC. Read the full text of the Article at 10.1002/batt.202100046.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The reduced aging at lower SOCs is in line with the calendar aging data reported in the literature. 27,[72][73][74] When evaluating the capacity retention of cells, the anode overhang equalization can cause significant capacity losses or recovery. [4][5][6] The relative behavior of capacity retention is often neglected and might not be representative of cell performance or quality.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced aging at lower SOCs is in line with the calendar aging data reported in the literature. 27,[72][73][74] When evaluating the capacity retention of cells, the anode overhang equalization can cause significant capacity losses or recovery. [4][5][6] The relative behavior of capacity retention is often neglected and might not be representative of cell performance or quality.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the phase transformation of the electrode in the process of Li+ intercalation/deintercalation, resulting in the formation of wave peaks on the DV curve. For lithium-ion batteries with Graphite/NCA system, according to relevant studies [17] , its DV curve has three obvious peaks, as shown in Figure 4(a, b). Peaks P1 and P2 are determined by the negative electrode, while P3 is determined by the positive electrode.…”
Section: The Analysis Of Differential Voltagementioning
confidence: 99%
“…Differential voltage (DV) analysis and Electrochemical impedance spectroscopy (EIS) analysis are common non-destructive characterization methods. Zulke et al [17] used the DV analysis method to study the degradation mode of Graphite/NCA batteries under a long rest time at different SOC and temperatures, they found that the main degradation mode of calendar aging was the loss of lithium ions caused by SEI film growth. Pastor-Fernandez et al [18] studied the aging mechanisms of Graphite/NCA batteries at room temperature using the EIS analysis method, and the results showed that lithium ions loss and active material loss played a dominant role in batteries' aging, while conductivity loss had little influence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the graphite anode of the lithium‐ion battery is theoretically unstable and easily undergoes redox reaction with the electrolyte, forming a passivation protective layer on the surface, that is, SEI 10 . SEI is usually formed during the formation stage of lithium‐ion batteries and the initial cycles and can act as a dense protective layer to reduce the further anode‐electrolyte reactions 11 . However, SEI will also grow during the operation of lithium‐ion battery, resulting in continuous capacity loss and impedance increase.…”
Section: Introductionmentioning
confidence: 99%